Board voting system based on the consortium blockchains - You-kang DONG; Da-wei ZHANG; Zhen HAN; Liang CHANG (网络与信息安全学报)
The board voting is a scenario of anonymous voting on a particular group of individuals,which is strict with the identities of the participants.A board e-voting protocol based on the consortium blockchains was presented,which replaced the traditional trusted third party with the smart contract so as to reduce the system trust cost.It adopt a digital certificate-based identity mechanism to ensure that the voter's identity is legal.It adopt the blind signature based on elliptic curve technology to achieve the anonymity of voting.The security analysis shows that the proposed protocol can meet the requirements of unforgeability,anonymity and security etc,which is convenient and flexible to use.